Cantharidin‐loaded functional mesoporous titanium peroxide nanoparticles for non‐small cell lung cancer targeted chemotherapy combined with high effective photodynamic therapy. Issue 6 (4th April 2020) - Zheng, Kun; Chen, Runze; Sun, Yanxue; Tan, Zhenquan; Liu, Ye; Cheng, Xiao; Leng, Junke; Guo, Zhaoming; Xu, Pengcheng
Abstract : Background: Although photodynamic therapy (PDT) has emerged as a potential alternative to conventional chemotherapy, the low reactive oxygen species (ROS) yield of the photosensitizer such as TiO2 nanoparticles has limited its application. In addition, it is difficult to achieve effective tumor treatment with a single tumor therapy. Methods: We used TiOx nanocomposite (YSA‐PEG‐TiOX ) instead of TiO2 as a photosensitizer to solve the problem of insufficient ROS generation in PDT. Benefiting from the desired mesoporous structure of TiOx, Cantharidin (CTD), one of the active components of mylabris, is loaded into TiOx for targeted combination of chemotherapy and PDT. The cellular uptake in human non‐small cell lung carcinoma cell line (A549) and human normal breast cell line (MCF 10A) was evaluated by confocal microscopy. in vitro cytotoxicity was evaluated using Cell Counting Kit‐8 assay. The ROS was detected via a chemical probe DCFH‐DA and the photodynamic treatment effect of YSA‐PEG‐TiOx was further evaluated by a living‐dead staining. The cell apoptosis was detected by the flow cytometry. Results: Our findings showed that the modification of YSA peptide improved the cytotoxicity of YSA‐PEG‐TiOX /CTD to EphA2 overexpressing A549 non‐small cell lung cancer (NSCLC) than non‐YSA modified counterparts. In addition, TiOx generated adequate ROS under X‐ray irradiation to further kill cancer cells. Flow analysis results also proved the superiority of this combined treatment. Conclusions: YSA‐PEG‐TiOX nanoparticles could significantly increase ROS production under X‐ray exposure and provide a new drug delivery nanocarrier for CTD in combination with PDT to achieve effective NSCLC treatment.